The persistence of form (and its omissions). A study of urban space in La Plata through its “analogues cities” - Ramiro Segura (Cuadernos de Antropología Social, 2009)
In this article, the city is designed as a space of representation. How to stabilize an image of the city? Why is that a multiplicity of heterogeneous and unequal actors tend to share similar representation of a city who use and experience differently? It attempts to answer these questions through analysis of laws and policies on the city, urban interventions and projects, pictures of the city, and maps and representations made by its inhabitants. It argues that the image of the city is the product of the sedimentation of a historical process in which urban and political elements are present, morphological, geographical and historical contexts. The public image is paradoxical in a town subject to various processes of transformation and, therefore, tends to omit elements of the city as we know it today.